2012
DOI: 10.1111/j.1476-5829.2012.00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic lymphangiographyin the dog using iodized oil

Abstract: The objective of this study was to develop a clinically applicable technique to visualize the medial retropharyngeal, superficial cervical, axillary, superficial inguinal and medial iliac lymph nodes on radiographs. Direct and indirect lymphangiographic methods using iodized oil were repeated for a minimum of five times at eight different locations to enhance the various lymph nodes, using 16 healthy research dogs. Direct lymphangiography, although more invasive than indirect lymphangiography, resulted in unif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…Injection was performed with a 25G needle into the four quadrants encircling the tumour. A slow rate infiltration (2–4 mL, over 1–5 min) was used as described previously . The injection was done in the tissue from which the mass was originating from or directly within the mass if it was not to change further surgical approach (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Injection was performed with a 25G needle into the four quadrants encircling the tumour. A slow rate infiltration (2–4 mL, over 1–5 min) was used as described previously . The injection was done in the tissue from which the mass was originating from or directly within the mass if it was not to change further surgical approach (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Indirect lymphography (IL) is defined as the deposit of a contrast medium in the periphery of lymphatic vessels in the view of being absorbed and drained by the lymphatic system . Imaging after contrast uptake [radiography, computed tomodensitometery (CT‐IL), ultrasonography or MRI], subsequently allows the identification of contrast enhanced lymph nodes and lymphatic vessels. Authors have reported the use of iodized oil (IO) for direct and IL in dogs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Described methods of pre-operative SLN mapping in veterinary medicine include lymphoscintigraphy,[14] contrast-enhanced ultrasonography,[6, 26] lipid-soluble iodinated contrast (LIC) with radiography 12,14,15 or computed tomography,[5, 7, 8, 27, 28] and water-soluble iodinated contrast (WIC) with computed tomography. [13, 2830] Lymphoscintigraphy requires special licensure and specialized equipment that limit the availability of this diagnostic technique.…”
Section: Introductionmentioning
confidence: 99%
“…While LIC can be used for radiographic evaluation and computed tomographic evaluation, LIC is expensive and can be difficult to obtain. Additionally, optimal imaging evaluation does not occur until 24 to 48 hours after administration[5,7] which adds additional cost and time.…”
Section: Introductionmentioning
confidence: 99%